Does Financial Development Lead to Poverty Reduction in China? Time Series Evidence - Ho, Sin-Yu; Iyke, Bernard Njindan (Journal of Economics and Behavioral Studies, 2017)
The impact of financial development on poverty reduction has received attention in the literature recently. While the connection between financial development and poverty may appear straight forward in theory, in empirics it may be much complicated. This study attempted at empirically assessing the causal links between financial development and poverty reduction in China for the period 1985â€“2014. The study used the Toda-Yamamoto causality test to avoid pretesting bias that has featured majority of the existing studies. The study utilized two standard proxies for financial development, namely: the domestic private credit by banks as percentage of GDP, and money supply (M2) as percentage of GDP; and a standard proxy for poverty reduction namely: the household final consumption expenditure per capita growth (annual percentage). The study found a bidirectional causal flow between financial development and poverty reduction, implying that the causal flow between these important variables is independent of the proxy for financial development. This means that financial sector reforms and poverty reduction programs are more of â€œwin-winâ€ strategies in the case of China. Therefore policymakers in China should continue to implement robust financial sector reforms and poverty reduction strategies.